Retracted: International Trade Path with Multi-Polarization based on Multidirectional Mutation Genetic Algorithm Enabled Neural Network - Intelligence and Neuroscience, Computational (Computational intelligence and neuroscience, 2023)
[This retracts the article DOI: 10.1155/2021/1370180.].[This retracts the article DOI: 10.1155/2021/1370180.].